2005
DOI: 10.1890/03-5029
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Spatial Pattern With Evenness Indices

Abstract: Quantifying the spatial distributions of organisms in simple and meaningful ways is important for understanding the ecology and habitat needs of species subject to anthropogenic disturbances. Most multi‐species conservation and management programs do not yet account for the variation of space‐use patterns exhibited by species preferring the same habitat type. To measure species' space‐use patterns as a step toward determining habitat needs, we suggest using evenness indices. Although commonly used in character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
0
31
0
2
Order By: Relevance
“…Simpson's evenness index ranges between 0 and 1 and is relatively unaffected by the rare species in the quadrat and by spatial distribution (Krebs 1999, Payne et al 2005. Data analysis.…”
Section: Elevation (Vertical)mentioning
confidence: 99%
“…Simpson's evenness index ranges between 0 and 1 and is relatively unaffected by the rare species in the quadrat and by spatial distribution (Krebs 1999, Payne et al 2005. Data analysis.…”
Section: Elevation (Vertical)mentioning
confidence: 99%
“…Simpson's evenness index ranges between 0 and 1 and is relatively unaffected by the rare species in the quadrat and by spatial distribution (Krebs 1999;Payne et al 2005). …”
Section: Sampling Designmentioning
confidence: 99%
“…These previous studies had reported the relative importance value of different arid and semi arid plants, their sensitivity index, their economic assessment and conservation priorities, different ecosystem services (cultural, provisional and regulatory) provided by them, quantification of the types and erosion of cultural transmission, medicinal plants primarily useful for various diseases related to different corporeal system like central nervous, gastro-intestinal, reproductive systems and the market analysis of certain plants in relation to their medicinal properties. Evenness: Evenness based on Shannon and Weaver and Simpson indexes were quantified according to Payne et al, 2005). While Simpson's index of diversity, measures the probability that two individuals selected at random from a sample will belong to same species were quantified according to Mathur (2014a).…”
Section: Methodsmentioning
confidence: 99%